Screening and Analysis of Anaplasma marginale Tunisian Isolates Reveal the Diversity of lipA Phylogeographic Marker and the Conservation of OmpA Protein Vaccine Candidate - Belkahia, Hanène; Ben Abdallah, Meriem; Andolsi, Rihab; Selmi, Rachid; Zamiti, Sayed; Kratou, Myriam; Mhadhbi, Moez; Darghouth, Mohamed Aziz; Messadi, Lilia; Ben Said, Mourad (Frontiers in Veterinary Science, 2021)
Bovine anaplasmosis caused by Anaplasma marginale is a disease responsible for serious animal health problems and great economic losses all over the world. Thereby, the identification of A. marginale isolates from various bioclimatic areas in each country, the phylogeographic analysis of these isolates based on the most informative markers, and the evaluation of the most promising candidate antigens are crucial steps in developing effective vaccines against a wide range of A. marginale strains. In order to contribute to this challenge, a total of 791 bovine samples from various bioclimatic areas of Tunisia were tested for the occurrence of A. marginale DNA through msp4 gene fragment amplification. Phylogeographic analysis was performed by using lipA and sucB gene analyses, and the genetic relationship with previously characterized A. marginale isolates and strains was analyzed by applying similarity comparison and phylogenetic analysis. To evaluate the conservation of OmpA protein vaccine candidate, almost complete ompA nucleotide sequences were also obtained from Tunisian isolates, and various bioinformatics software were used in order to analyze the physicochemical properties and the secondary and tertiary structures of their deduced proteins and to predict their immunodominant epitopes of B and T cells. A. marginale DNA was detected in 19 bovine samples (2.4%). Risk factor analysis shows that cattle derived from subhumid bioclimatic area were more infected than those that originated from other areas. The analysis of lipA phylogeographic marker indicated a higher diversity of Tunisian A. marginale isolates compared with other available worldwide isolates and strains. Molecular, phylogenetic, and immuno-informatics analyses of the vaccine candidate OmpA protein demonstrated that this antigen and its predicted immunodominant epitopes of B and T cells appear to be highly conserved between Tunisian isolates and compared with isolates from other countries, suggesting that the minimal intraspecific modifications will not affect the potential cross-protective capacity of humoral and cell-mediated immune responses against multiple A. marginale worldwide strains.